A review on strategies for the fabrication of graphene fibres with graphene oxide. Issue 10 (5th February 2020) - Yin, Fei; Hu, Jianchen; Hong, Zhenglin; Wang, Hui; Liu, Gang; Shen, Jun; Wang, Hsing-Lin; Zhang, Ke-Qin
Abstract : The commonly used strategies for the fabrication of graphene fibres via graphene oxide are systematically reviewed. Abstract : Graphene fibres have been recognized as ideal building blocks to make advanced, macroscopic, and functional materials for a variety of applications. Direct fabrication of graphene fibres with ideal graphene sheets is still far from reality due to the weak intermolecular bonding between graphene sheets. In contrast, the construction of graphene oxide fibres by following a reduction process is a common compromise. The self-assembly of graphene oxide is an effective strategy for the continuous fabrication of graphene fibre. Different fabrication strategies endow graphene fibres with different performances. Over the past decade, various studies have been carried out into integrating graphene oxide nanosheets into graphene fibres. In this review, we summarize the assembly methods of graphene fibres and compare the mechanical and electrical performances of the graphene fibres fabricated by different strategies. Also the influence of the fabrication strategy on mechanical performance is discussed. Finally, the expectation of macroscopic graphene fibres in the future is further presented.